A high‐density, SNP‐based consensus map of tetraploid wheat as a bridge to integrate durum and bread wheat genomics and breeding. Issue 5 (26th November 2014) - Maccaferri, Marco; Ricci, Andrea; Salvi, Silvio; Milner, Sara Giulia; Noli, Enrico; Martelli, Pier Luigi; Casadio, Rita; Akhunov, Eduard; Scalabrin, Simone; Vendramin, Vera; Ammar, Karim; Blanco, Antonio; et al.
Summary Consensus linkage maps are important tools in crop genomics. We have assembled a high‐density tetraploid wheat consensus map by integrating 13 data sets from independent biparental populations involving durum wheat cultivars (Triticum turgidum ssp. durum), cultivated emmer (T. turgidum ssp. dicoccum) and their ancestor (wild emmer, T. turgidum ssp. dicoccoides). The consensus map harboured 30 144 markers (including 26 626 SNPs and 791 SSRs) half of which were present in at least two component maps. The final map spanned 2631 cM of all 14 durum wheat chromosomes and, differently from the individual component maps, all markers fell within the 14 linkage groups. Marker density per genetic distance unit peaked at centromeric regions, likely due to a combination of low recombination rate in the centromeric regions and even gene distribution along the chromosomes. Comparisons with bread wheat indicated fewer regions with recombination suppression, making this consensus map valuable for mapping in the A and B genomes of both durum and bread wheat. Sequence similarity analysis allowed us to relate mapped gene‐derived SNPs to chromosome‐specific transcripts. Dense patterns of homeologous relationships have been established between the A‐ and B‐genome maps and between nonsyntenic homeologous chromosome regions as well, the latter tracing to ancient translocation events. The gene‐based homeologous relationships are valuable to infer the map location of homeologs of target loci/QTLs. Because most SNP and SSR markers were previously mapped in bread wheat, this consensus map will facilitate a more effective integration and exploitation of genes and QTL for wheat breeding purposes.